Facile fabrication of p-Cu2O/n-ZnO nanorods arrays heterojunction ultraviolet sensor by aqueous method. (10th October 2018) - Liu, Juan; Yu, Naisen; Qi, Yan; Zhao, Haiyan; Yuan, Qing; Cao, Liwei
Abstract: The p-Cu2 O/n-ZnO heterojunction structure was prepared using low temperature aqueous way. The heterojunction structure composed of Cu2 O flower-like nanostructures and ZnO nanorod arrays (NRs). Meanwhile, simple ultraviolet (UV) detector device based on the p-Cu2 O/n-ZnO heterojunction structure was fabricated. The photoresponse results showed that the device was sensitive to UV light illumination, and it has good stability and reproducibility. The heterojunction can simultaneously promote the charge transport and enhance the surface area. The result will provide a promising way to fabricate high performance UV photodetectors based on p-Cu2 O/n-ZnO heterojunction with low cost.